Unpacking pre-service teachers’ beliefs and reasoning about student ability, sources of teaching knowledge, and teacher-efficacy: A scenario-based approach - Ferguson, Leila E.; Bråten, Ivar (Frontiers in Education, 2022)
The beliefs teachers hold may provide information about their more or less evidence-informed reasoning about educational issues. However, gaining a clear picture of teachers’ beliefs has proven difficult. A promising line of inquiry uses scenario-based approaches to assess teachers’ enacted beliefs. Accordingly, we assessed 75 Norwegian pre-service teachers’ beliefs about student ability, sources of teaching knowledge, and teacher efficacy by analyzing their written responses to authentic classroom scenarios, with these responses also providing information about participants’ reasoning about the scenarios. While participants’ responses seemed to be evidence-informed in many ways, there were also indications of the opposite, such as limited consideration of educational research in pedagogical decision-making. The results contribute uniquely to an understanding of pre-service teachers’ beliefs and reasoning about educational issues. As such, they may help researchers and teacher educators to better understand the beliefs pre-service teachers hold, as well as to facilitate further development of these beliefs. Implications for future research and teacher education are discussed.